Engineering Gene Therapy: Advances and Barriers. Issue 9 (20th June 2021) - Shahryari, Alireza; Burtscher, Ingo; Nazari, Zahra; Lickert, Heiko
Abstract: Currently, 33 gene‐therapy drugs/products have been approved in the clinic. Over 3000 completed and ongoing clinical gene therapy trials have been reported worldwide. The development/maturation of tools for gene manipulation and gene delivery, as well as molecular advances in the diagnosis of genetic diseases, have played a central role in gene therapy, which have greatly revolutionized the field. Versatile and diverse genetic tools for gene manipulations and deliveries, with the possibility of short and long‐term effects, are vital advantages of gene therapy tools, paving the road for the development of new therapies. However, efficacy and safety concerns, immune system responses, laborious approaches for developing and manufacturing, unknown gene‐therapy drug interactions with the host and the high cost of drugs/products, are significant barriers in gene therapy. Here, the authors review the attempts for engineering of the gene manipulations that have been undertaken in the last three decades and used in clinical trials focusing on 1) gene‐editing platforms, 2) viral gene delivery systems, and 3) nonviral gene tools. In this comprehensive review, the principles of these gene manipulation tools as well as advances and barriers for their application in modern therapies are discussed. Furthermore, trends and future directions in gene therapy are discussed. Abstract : This review discusses genetic tools, which have been used in clinical gene therapy trials during the last three decades. These tools include gene‐editing platforms, viral gene delivery vehicles, and nonviral tools. Furthermore, their advances and barriers as well as trends and future directions in modern gene therapy are emphasized.